Echo and Critique : Poetry and the Clichés of Public Speech - Gargaillo, Florian (Book collections on Project MUSE., 2023)
"In Echo and Critique, Florian Gargaillo tells a new story about the ways that poets living in the United States apprehended the cliches of public speech in the four decades following the start of World War II. During this period, many intellectuals lamented that public discourse had become saturated with abstract stock phrases such as "the fight for freedom," "revenue enhancement," or "service the target" that are bureaucratic in origin, designed for the mass media, and used to euphemize, obfuscate, and evade. As Gargaillo shows, poets responded to these political cliches with a major yet little discussed method that he calls "echo and critique," whereby they would quote discrete stock phrases in their poems, and then use the structure, tone, rhythm, and imagery of the surrounding context to study their implications and weigh their effects. The goal was not simply to dismiss these phrases, but to better understand their effectiveness, recognize the values they promote, and identify the realities they might seek to distort or suppress. The book moves chronologically from 1939 to the end of the Vietnam War and shows the evolution of echo and critique across four formative decades. While charting the pervasiveness of this method following the start of World War II, Gargaillo also examines in depth the crisis of conscience that public cliches generated for individual poets including W. H. Auden, Randall Jarrell, Langston Hughes, Claude McKay, Robert Lowell, Josephine Miles, and Seamus Heaney. A dynamic literary and cultural study of postwar American poetry, Echo and Critique reveals how poets challenged the language that those in power deploy to achieve political ends"--